China's real estate sector and the impacts of its possible disorder on Chinese economy and the euro area - Juuso Kaaresvirta; Eeva Kerola; Riikka Nuutilainen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
China's real estate and construction sector has served as a major engine of economic growth in recent decades and the sector now plays an oversized role in the economy. Much of that growth has been debt-fuelled, with the indebtedness of developers climbing to unprecedented levels. After officials turned off the money spigot last year, housing markets cooled and a wave of financial difficulties washed over builders during autumn 2021. The entire sector found itself under heavy stress, and in December two major developers, Evergrande and Kaisa, defaulted on their offshore debt. In this brief, we consider the current conditions in China's real estate and construction sector and how a possible sectoral crisis could spread to the national economy and the euro area. While the direct financial impacts on the euro area's financial sector is likely to be minor, China's real estate sector problems could spill over widely into the domestic real economy and thereby increase uncertainty internationally. In such case, the indirect impacts on the euro area could be severe.
urn:nbn:fi:bof-202112162156
Keywords: 330; China; risks; real estate sector; construction; economy; economic growth